(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
This article analyzes how the competencies of future teachers in information and communication technologies (ICT) can be developed in the process of managing project activities and mutual collaboration. ICT competencies provide teachers with the opportunities to effectively organize the educational process, manage students’ activities, and develop interpersonal interactions. The article discusses the necessary methodological approaches, creative pedagogical methods, and ways to apply innovative technologies to enhance ICT competencies.